3D Printed Robotic Assembly Enabled Reconfigurable Display with Higher Resolution. Issue 12 (28th September 2018) - Qaiser, Nadeem; Khan, Sherjeel Munsif; Chow, Kelvin; Cordero, Marlon Diaz; Wicaksono, Irmandy; Hussain, Muhammad Mustafa
Abstract: The stretchable display might play a crucial role in transforming many potential applications including wearable electronics, flexible displays for smart TV/devices, health monitoring wristbands, and illumination systems. To date, the most commonly used stretchable displays include the installation of light‐emitting diodes (LEDs) onto a compliant substrate. However, they have critical limitations such as an increase in resistance and degradation of pixel resolution due to growing gaps between LEDs. Here, a reversible stretchable platform is demonstrated, which preserves not only the resistance of LEDs but also the pixel resolution of the display. Our stretchable platform utilizes the concept of the multilevel arrangement of LEDs, which are mechanically guided by joint pins/links to move out‐of‐plane and fill the evolved gap. To corroborate the concept of the reconfigurable display, the reconfigurable platform is manufactured by using a 3D printer. Our design might be a key enabling technology to next‐generation expandable display and illuminations systems. Abstract : A reversible and reconfigurable display is proposed, which utilizes the novel concept of multi‐level arrangement of light‐emitting diodes (LEDs). The proposed platform caters for the problem of distorted display/image quality during stretching by preserving the actual resolution of the display. It also does not change the resistance of LEDs. 3D printed platform was tested and compared with the finite element methods (FEM) results.